Importance of Multi-disciplinary Tumor Boards during the COVID-19 Global Pandemic in a Resource Constrained Country - Velu, Umesh; Shetty, Preethi S; M Godkhindi, Vishwapriya (Asian Pacific Journal of Cancer Biology, 2022)
Background: Multidisciplinary tumor boards (MDTB) are an integral part of cancer management. However, owing to COVID 19 global pandemic it becomes a challenge to have a MDTBs maintaining the social distance norms. Objectives: To assess the technical challenges faced during a virtual tumor board (VTB) discussion Advantages and Disadvantages of a VTBs. Methods: Technical support for various group meetings taking place virtually were considered. Various trials which have assessed the technical difficulties for conducting such a meeting were assessed. The advantages and disadvantages for using various platforms of social media for such a virtual meeting were assessed and various feedbacks and reviews were taken into consideration. Results: VTBs can be implemented either by a video conferencing or web based conferencing. High speed internet connections of 4 mbps for a 30fps at 4k monitor would be required for smooth lag free interaction. The processors should have a minimum of 2 GB of RAM with quad core processor. Platforms which offer the ability for digital signatures are of paramount importance. Having a VTBs during a global pandemic is of paramount importance for a cancer patient. Conclusion: VTBs are very important for management of cancer patients during a global pandemic. We in our paper have tried to summarize the technical support need for such a platform and also have tried to discuss the advantages and disadvantages of such a platform. We would also like to conclude that setting up such a virtual platform is not technically challenging and can be implemented in smaller centers even through a mobile phone connection. VTBs should be implemented in all cancer centers during a pandemic when in person meetings are a challenge and a health risk.